Emergency Department Use of the HINTS Exam. (October 2022) - Engler, Kristiana; Wood, John; Cook, Calli
Abstract : The Research to Practice column is designed to improve translational research critique skills of advanced practice nurses (APNs). In this issue, the article "Diagnostic Accuracy of the HINTS Exam in an Emergency Department: A Retrospective Chart Review" is discussed in the context of a patient presenting to the emergency department (ED) with acute dizziness. The study was designed to assess the efficacy and appropriate use of the HINTS exam in the ED. Assessing and evaluating dizziness is complex, and with the growing cost associated with the ED assessment of dizziness, appropriate use of the HINTS exam could reduce cost. APNs need to be aware of the appropriateness of use when administering the HINTS exam and how to interpret the findings from the assessment. Improved awareness and education regarding the HINTS exam could streamline the workup of vertigo and dizziness in the ED.